Perfil epidemiológico de zoonoses nos municípios afetados diretamente pela usina hidrelétrica Estreito (MA) - Gomes, Helierson (2014)
By constant anthropic actions, resulting in several segments imbalance, such as, environmental, social and health service, we carried out a study to evaluate the influence that the construction of HPP Estreito, in Maranhão, Brazil, had on the rate of zoonotic diseases in the provinces of Carolina and Estreito (MA). As a method, we compared the records of the average incidence, in each province, covering the period that preceded the power plant s construction (2001-2005), the period throughout the construction (2006-2010) and after the building was completed (2011- 2012); highlighting epidemiological zoonotic diseases, such as Dengue, leishmaniasis, visceral leishmaniasis, Chagas disease, yellow fever and malaria. Dengue, with 907 incidents had the highest morbidity rate. In the course of the HPP construction, the province of Carolina presented an increase of 1.75% in its dengue cases and Estreito presented an increase of 1.59%. Leishmaniasis, with 175 cases notified, presented a higher occurrence in the period during the construction. Before the construction, rates were of 0.39% in Carolina and 0.47% in Estreito. Visceral leishmaniose, with 91 cases notified, increased in Carolina throughout the HPP construction by 0.27%. After the complete filling of the lake, Estreito presented an increase of 0.16% in its visceral leishmaniose cases. Chagas disease, yellow fever and malaria had not presented any cases, in the provinces where the study was held. The research does not suggest that there is a direct connection between the HPP construction and epidemiological changes considered in this research.